2011
DOI: 10.2478/s11535-011-0058-0
|View full text |Cite
|
Sign up to set email alerts
|

Giant cell formation: the way to cell death or cell survival?

Abstract: The study of giant cells in populations of different tumor cells and evaluation of their role in cancer development is an expanding field. The formation of giant cells has been shown to be followed by mitotic catastrophe, apoptosis, necrosis, and other types of cell elimination. Reports also demonstrate that giant cells can escape cell death and give rise to new cancer cells. However, it is not known if the programmed cell death is involved in this type of cell cycle disorders. Here we describe principal event… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 67 publications
(79 reference statements)
0
9
0
Order By: Relevance
“…Studies showed that polyploid giant cells have the ability to chromatid exchange and probably the production of a fully repaired chromosome. Moreover, homologous chromosomes from the giant cell can be relocated and paired which is the step to depolyploidization ( 47 , 48 ). Silencing of LMNB1 affects DNA damage and repair pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Studies showed that polyploid giant cells have the ability to chromatid exchange and probably the production of a fully repaired chromosome. Moreover, homologous chromosomes from the giant cell can be relocated and paired which is the step to depolyploidization ( 47 , 48 ). Silencing of LMNB1 affects DNA damage and repair pathway.…”
Section: Discussionmentioning
confidence: 99%
“…The giant cells exhibiting pleomorphism of the nuclei predicts bad prognosis of the tumour. [ 15 16 17 ]…”
Section: Giant Cellsmentioning
confidence: 99%
“…The relationship between PGCCs and senescent cells is still a matter of discussion, whereby also a standardized nomenclature is missing. PGCCs have been described as nondividing flattened tumor cells that are irreversibly arrested either in the G0/G1 or G2/M state and express β -galactosidase activity [ 8 , 9 ]. On the contrary, PGCCs have also been characterized as not senescent due to the lack of β -galactosidase staining [ 10 ].…”
Section: Introductionmentioning
confidence: 99%